Spain and Pandemic COVID-19: State of alarm to Climate Lacking in Various Aspects - Firsty Chintya Laksmi Perbawani (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2020)
Tulisan ini membahas bagaimana Spanyol merespon fenomena pandemi COVID-19. Fokus dimulai pada awal kemunculan virus yang mendorong pemerintah mengeluarkan kebijakan dengan empat lokus utama: (1) general confinement atau upaya pelarangan masyarakat keluar rumah; (2) penghentian beberapa kegiatan ekonomi; (3) penyediaan sumber daya kesehatan; dan (4) penyusunan kebijakan mitigasi lanjutan. Penulis melihat pola respon yang terjadi cenderung reaktif daripada antisipatif. Walaupun berbagai langkah strategis sudah dilakukan, hingga akhir Juni 2020, Spanyol gagal membendung kurva sehingga menjadi salah satu negara Eropa terburuk dengan total lebih dari 240.000 kasus. Penulis berargumen faktor kontributornya adalah adanya lacking climate atau iklim serba “kekurangan” di berbagai aspek, sehingga menyebabkan Spanyol menjadi episentrum virus. Kekurangan dapat dilihat secara empiris pada aspek manajemen politis yang asimetris antara pemerintah pusat dengan pemerintah lokal di tujuh belas komunitas otonom; aspek teknologi pengumpulan data yang paradoks; aspek pelayanan kesehatan yang bermasalah; hingga aspek organisasional di tataran Uni Eropa yang mengaburkan fokus Spanyol untuk seharusnya membenahi keadaan nasionalnya terlebih dahulu. Tulisan ini membuktikan bahwa koordinasi menjadi hal yang sangat krusial bagi Spanyol dalam menghadapi krisis kesehatan global, COVID-19.Kata kunci: Spanyol, pandemi, COVID-19, state of alarm, normalitas baru This paper discusses how Spain has responded to the COVID-19 outbreaks. The focus of discussion began when virus emergences which prompted the government to issue policies with four main focus: (1) general confinement or efforts to prohibit people from leaving the house; (2) cessation of some economic activities; (3) provision of health resources; and (4) preparation of advanced mitigation policies. The author sees that the response pattern tends to be reactive rather than anticipatory. Although various strategic steps have been taken, Spain failed to stem the curve until the end of June 2020. Therefore, it became one of the worst European countries, with more than 240.000 cases. The author argues that the contributing factor is “lacking climate” in various aspects, causing Spain to become the epicenter of the virus. The shortcomings can be seen empirically in the asymmetric characteristics of political management, between the central government and local government in seventeen autonomous communities; paradoxical aspects of data collection technology; problematic aspects of health services; to the organizational part at the level of the European Union which obscures the focus of Spain on what should first fix its national situation. This paper proves that coordination is very crucial for Spain in facing the global health crisis, COVID-19.Keywords: Spain, pandemic, COVID-19, state of alarm, a new normality